2022
DOI: 10.1002/pat.5678
|View full text |Cite
|
Sign up to set email alerts
|

Extraction processes for deriving cellulose: A comprehensive review on green approaches

Abstract: Cellulose is a renewable, biodegradable and thermally stable compound with several other strong and attractive properties. Cellulose being most abundant raw material on earth has been also produced commercially through several plants every year because of its substantial involvement in variety of potential applications. Cellulose and its derivatives can be employed in paper, textile industry, and food industry along with its utilization in pharmaceutical and biomedical applications. Such applications entail th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…The presence of those forces is the determining factor resulting in the preferred stereo arrangement of the particle. 20 Infrared spectroscopy (IR) 23,24 as well as subsequent 13 C NMR analyses 25 confirmed that the -OH group in the C3 position and the adjacent pyranose oxygen atom form the intramolecular hydrogen bond, similar to the C2 and C6 hydroxyl groups. Together with the β-(1,4)-glycoside bonds, those interactions are responsible for the cellulose's remarkable mechanical propertiesespecially its rigidity and hardness.…”
Section: Chemical Structure Of Cellulosementioning
confidence: 84%
See 3 more Smart Citations
“…The presence of those forces is the determining factor resulting in the preferred stereo arrangement of the particle. 20 Infrared spectroscopy (IR) 23,24 as well as subsequent 13 C NMR analyses 25 confirmed that the -OH group in the C3 position and the adjacent pyranose oxygen atom form the intramolecular hydrogen bond, similar to the C2 and C6 hydroxyl groups. Together with the β-(1,4)-glycoside bonds, those interactions are responsible for the cellulose's remarkable mechanical propertiesespecially its rigidity and hardness.…”
Section: Chemical Structure Of Cellulosementioning
confidence: 84%
“…Because of that cellulose II is much less reactive, more durable and far more widely found than cellulose I. 26 Crystal structures of cellulose Nuclear magnetic resonance 13 C NMR and X-ray diffraction research techniques proved that cellulose exhibits a certain level of crystallinity. At the same time, a number of inconsistencies in the crystalline structure were discovered.…”
Section: Chemical Structure Of Cellulosementioning
confidence: 99%
See 2 more Smart Citations
“…Fibers were obtained by submitting the industrial rice crop to alkali (NaOH) and bleaching treatments. Nanocrystals were extracted from these fibers using sulfuric acid (H 2 SO 4 ) hydrolysis treatment [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%